Tecnologia da informação, discurso e poder: análise de domínio a partir do conceito de exclusão digital na perspectiva da teoria centro-periferia - Berrío-Zapata, Cristian [UNESP] (2015)
This research aims to study the Digital Divide as part of the discourse from the meta-narratives emerged in the XXI century, which form part of the construction of globalization, supported in information technology (IT) and computer networks. The Information Society as a meta-narrative from this historic moment, rescued elements belonging to the European Enlightenment at the industrial age and the American Fordism, that combined with the role of IT and through a series of connotations and mythifications, bailed the neo-capitalist order whose center is the US. This order, as described by the Center-Periphery Theory, maintains and increases the dependency phenomenon in developing countries, by means of economic, technological and discursive mechanisms that work within a vision of Soft Power. The Digital Divide is one of these discourses, that helps legitimizing the passive and uncritical inclusion of all territories within the digital structure, spreading forms of Electronic Colonialism. This research looked for empirical evidence of this process in the academic construction of narratives about the Digital Divide, by examining a sample of the most cited literature of the field in English, as a representative of the Center countries, and Spanish and Portuguese as representatives of the academies from the Periphery. We used Domain Analysis as methodology, including four types of study: Study of Literature and Sources, Historical, Bibliometric and a Critical & Epistemological study. The document sample was collected using Google Scholar. This work applies the perspective of Critical Theory and Grounded Theory from a systemic, ecological and complexity perspective. The results showed large differences of production and citation between the three communities, with the USA retaining more than 70% of production and citation. The Anglophone community has the publication of its literature dominated by large corporations, which limits free access...